(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: Age and sex are the most significant primary characteristics in identifying an individual and have considerable medicolegal importance in the administration of justice. The approximate age of an individual can be estimated by correlation of physical, dental and skeletal development. The present study has been undertaken to study the scientific estimation of age from the fusion of bone epiphysis of elbow joint, wrist proper perspective. Methodology: The study was conducted on 100 sports persons aged between 9 to 18 years came for age estimation and sent by various State Association approved by the sports authority of India. Each of these subjects was radiographed for elbow joint, wrist joint, hip joint and ossification centres were studied for appearance and fusion. The gender was analysed and compared by mean rank, sum of ranks and P- Value using ‘Mann-Whitney test.’ Results: The age of fusion in males is greater than that in females for medical epicondyle, lateral epicondyle, conjoint epiphysis, humerus, the lower end of radius, lower end of ulna, Triradiate cartilage, iliac crest, head of femur, Upper end of femur with shaft and appearance of carpal bones.